Peningkatan Kinerja Guru Dalam Pembelajaran Di Kelas Melalui Supervisi Edukatif Kolaboratif Secara Periodik - N. Siti Saodah (Universitas Mathla'ul Anwar Banten, 2020)
This study aims to describe the steps of collaborative educational supervision periodically in implementing learning, in assessing learning achievement, in carrying out follow-up assessments of student achievement and in preparing learning plans that will support the improvement of teacher performance. This type of research is a school research aimed at teachers so through educational supervision, PKG, anddiscussion. can periodically improve the performance and insight of teachers at Citumenggung State Elementary School 3